A case of spontaneous spinal epidural hematoma mimicking transient ischemic attack. (15th September 2022) - Liu, Cong; Liu, Xiuli; Liu, Yan; Ma, Guomei; Li, Hui; Han, Jingzhe; Xiang, Yi
Abstract: Spontaneous spinal epidural hematoma (SSEH), a disease with exact etiology unknown, is characterized by acute onset of neck or back pain and rapidly progressive nerve root or spinal cord compression. It is rare in clinical practices, with a prevalence of approximately one in a million. Due to the lack of population-based epidemiological survey data for SSEH, clinicians have a serious lack of understanding of the disease and are prone to miss the best time for treatment, leaving patients with neurological dysfunction which is difficult to recover. In this paper, we report a case of SSEH with rare clinical manifestations, to improve clinicians' understanding of SSEH. The patient was mainly characterized by episodic left lower limb weakness and had been misdiagnosed as TIA.